Social Media Practices and Patient Interactions Among Healthcare Professionals [13G]. Issue 1 (May 2017) - Davis, Jay; Tompkins, Emily; Chen, Lian; Lai, Monica; Hagan, Joseph; Stafford, Irene
Abstract : INTRODUCTION: Social media (SM) has become widespread among healthcare professionals (HCPs) including attending-physicians, residents and medical students. It is unknown if engagement in social activity with patients on SM differs according to level of training. This study was conducted to survey HCPs on their SM practices as it pertains to personal disclosure and patient interactions. METHODS: A survey was conducted among HCPs pertaining to SM usage and patient-friendship requests. The chi-square test was used to compare different occupations' frequency of and response to patient-friendship requests and disclosure of personal information on SM. SAS version 9.4 was used for analysis. A 5% significance level was used for hypothesis tests. RESULTS: Six hundred forty-six participants responded: 524 (81%) medical students, 91 (14%) residents, 25 (4%) attending-physicians, and 6 (1%) unknown. The proportion of respondents who display a personal photograph (59% of attending-physicians vs. 93% for other HCPs, p < 0.001) or their name on their SM profile (55% of attending-physicians vs. 84% for other HCPs, p < 0.001) differed by occupation with attending-physicians least likely to do so. The proportion of respondents reporting that they have received a patient-friendship request differed significantly with attending-physicians most likely to have received a request (36% vs 4% for other HCPs, p < 0.001) and students most likely to decide on an individual basis or accept (41% of students vs. 22% for other HCPs, p < 0.001). CONCLUSION: Although attending-physicians were more likely to receive a patient-friendship request, they were less likely to accept and disclose personal information on SM demonstrating concern for safety.